222k views
0 votes
Find all solutions of

Find all solutions of-example-1

1 Answer

3 votes

Answer:
x=n\pi +(-1)^n(\pi)/(6),
x=n\pi +(-1)^n\left((-\pi)/(6)\right)

Explanation:

Given


\sin x-√(1-3\sin^2x)=0

Take the square root term to the right-hand side


\Rightarrow \sin x=√(1-3\sin^2x)\\\text{Squaring both sides}\\\Rightarrow \sin^2x=1-3\sin^2x\\\Rightarrow 4\sin^2x=1\\\\\Rightarrow \sin^2x=(1)/(4)\\\\\Rightarrow \sin x=\pm(1)/(2)

for


\sin x=(1)/(2)


x=n\pi +(-1)^n(\pi)/(6)

for


\sin x=(-1)/(2)


x=n\pi +(-1)^n\left((-\pi)/(6)\right)

User Miron Brezuleanu
by
5.2k points